2021
DOI: 10.1111/tbed.14305
|View full text |Cite
|
Sign up to set email alerts
|

Research effort on birds’ reservoir host potential for Lyme borreliosis: A systematic review and perspectives

Abstract: Zoonotic tick‐borne diseases threat human and animal health. Understanding the role of hosts in the production of infected ticks in an epidemiological system is essential to be able to design effective measures to reduce the exposure of humans and animals to infectious tick bites. The reservoir host potential, that is, number of infected ticks produced by a host species, depends on three components: tick production, realized reservoir competence and host density. The parameters and factors that determine the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Further, we found that individual bird infection communities were characterized by greater genotype co-occurrence, indicating facilitation, in contrast with mammal communities that appear to exhibit only competitive interactions among genotypes. These findings may be partially explained by birds' longer lifespan, different immunity mechanisms, larger home ranges, or other life-history traits resulting in more opportunities for infection (Rataud et al 2021). Thus, our study emphasizes the role of passerine birds in maintaining Bb transmission and increasing human disease risk locally, in addition to their known roles as reservoir hosts and tick dispersers (Ginsberg et al 2006;Brinkerhoff et al 2010Brinkerhoff et al , 2011Vuong et al 2014;Loss et al 2016;Becker & Han 2021).…”
Section: Host Community Composition Drives Patterns Of Bb Diversity I...mentioning
confidence: 78%
See 1 more Smart Citation
“…Further, we found that individual bird infection communities were characterized by greater genotype co-occurrence, indicating facilitation, in contrast with mammal communities that appear to exhibit only competitive interactions among genotypes. These findings may be partially explained by birds' longer lifespan, different immunity mechanisms, larger home ranges, or other life-history traits resulting in more opportunities for infection (Rataud et al 2021). Thus, our study emphasizes the role of passerine birds in maintaining Bb transmission and increasing human disease risk locally, in addition to their known roles as reservoir hosts and tick dispersers (Ginsberg et al 2006;Brinkerhoff et al 2010Brinkerhoff et al , 2011Vuong et al 2014;Loss et al 2016;Becker & Han 2021).…”
Section: Host Community Composition Drives Patterns Of Bb Diversity I...mentioning
confidence: 78%
“…Further, we found that individual bird infection communities were characterized by greater genotype co-occurrence, indicating facilitation, in contrast with mammal communities that appear to exhibit only competitive interactions among genotypes. These findings may be partially explained by birds’ longer lifespan, different immunity mechanisms, larger home ranges, or other life-history traits resulting in more opportunities for infection (Rataud et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Further, individual bird infection communities were characterized by greater genotype co-occurrence, indicating facilitation, in contrast with mammal communities that appear to exhibit only competitive interactions among genotypes. These findings may be partially explained by birds' longer lifespans, different immunity mechanisms, larger home ranges, or other life-history traits resulting in more opportunities for infection ( 76 ). Thus, our study emphasizes the role of passerine birds in maintaining Bb transmission and increasing human disease risk locally, in addition to their known roles as reservoir hosts and tick dispersers ( 18 , 45 , 74 , 77–79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hard ticks (Ixodidae) are vectors of several pathogens, such as Rickettsia spp., Borrelia spp., and Crimean-Congo Hemorrhagic Fever virus (CCHFV) [50][51][52]. In Europe and the Mediterranean, most ticks found on avian species are immature stages from the genus Hyalomma, Ixodes ticks of all stages and, sporadically, immature stages from the genera Haemaphysalis and Rhipicephalus [52,53].…”
Section: Ticksmentioning
confidence: 99%